Optical coherence tomography angiography in preclinical Alzheimer's disease. Issue 2 (22nd May 2019) - van de Kreeke, Jacoba Alida; Nguyen, Hoang-Ton; Konijnenberg, Elles; Tomassen, Jori; den Braber, Anouk; ten Kate, Mara; Yaqub, Maqsood; van Berckel, Bart; Lammertsma, Adriaan A; Boomsma, Dorret I; Tan, Stevie H; Verbraak, Frank; et al.
Abstract : Background/aims: As a protrusion from the brain, the retina might reflect the status of the brain. Previous studies showed a decrease in vessel density and foveal avascular zone (FAZ) enlargement on optical coherence tomography angiography (OCTA) in individuals suffering from Alzheimer's disease (AD). This study aims to assess whether such changes are already present in preclinical stages of AD, in a population of monozygotic (MZ) twins. Methods: 124 cognitively healthy individuals (MZ twins, ages 60–93 years) underwent [ 18 F]flutemetamol amyloid positron emission tomography (PET) scanning and OCTA. PET scans were visually rated for cortical amyloid-beta (Aβ) positivity. Parametric global cortical non-displaceable binding potential ( BP ND ) was used as a continuous measure for Aβ aggregation. FAZ size and vessel densities for the inner and outer ring of the macular ETDRS grid and in a 3–6 mm ring around the optic nerve head (ONH) were measured. OCTA measures were associated with visual Aβ score, BP ND and amyloid load estimated by twin concordance on visual Aβ score. Twin correlations were estimated as a measure of maximum heritability of OCTA measures. Results: 13 of 124 participants were Aβ+. Aβ+ individuals had significantly higher vessel density than Aβ– individuals in all regions but did not differ in FAZ size. Twin analyses showed a positive association between and vessel densities in all regions. BP ND tended to be associated with higher vessel density in the inner ring. Twin correlations were moderate/high for all OCTA parameters except vessel density around the ONH, which correlated weakly. Conclusion: Retinal vessel density was higher in individuals with preclinical AD.